The Significance of Duration of Exposure and Circulation of Fresh Air in SARS-CoV-2 Transmission Among Healthcare Workers - Vlacha, Vasiliki; Feketea, Gavriela; Petropoulou, Athanasia; Trancá, Sebastian Daniel (Frontiers in Medicine, 2021)
Background: The true risk of infection after exposure to SARS-CoV-2 of health care workers (HCWs) in the workplace has not yet been established. This descriptive study analyzes the exposure characteristics of HCWs to SARS-CoV-2. Methods: In March 2020, at the beginning of the pandemic, a total of 58 HCWs in a regional hospital in Greece were exposed to 3 patients with symptomatic SARS-CoV-2 infection. These 3 index cases had taken part in an 8-day religious tour, during which 52 travelers spent 10 hours every day in a tour bus. A study was made of the circumstances of the hospital exposure. Results: Of the 52 travelers in the bus, 48 contracted SARS-CoV2. None of the 58 HCW contacts developed symptoms related to COVID-19, although 43% were exposed to a SARS-CoV-2 infected patient for more than 15 min, and 74% were within a distance of less than 1 meter, and half of the contacts were not wearing a surgical mask. Additional information was that 63% of the contacts were exposed in a room sized more than 15 m2, and in more than 80% of cases, the window or the door to the room was open during their exposure. In about one third of the exposure events, the HCW contacts were not wearing a mask and were at a distance of less than 1 meter, and just under half of them were exposed for more than 15 min. One fourth of the contacts underwent RT-PCR testing, and 11% IgG/IgM antibody testing for SARS-CoV-2, all of which were negative. All observed quarantine at home for 14 days. Conclusion: This observational study was made before the extent of the SARS-CoV-2 became apparent, and before routine preventive measures were observed by all HCWs. Comparing the conditions of exposure in the two different settings (bus vs regional health facility), it is apparent that the duration of exposure and the small, enclosed nature of the bus are the distinguishing factors. In the health care setting the elimination of both factors and the implementation of additional measures protected the exposed HCWs from contracted SARS-CoV-2 infection.